Experiences of designing women: a portrait of female interior designers' job satisfaction across career-spans - Goodnite, A. Elizabeth, author; Malinin, Laura, advisor; Ogle, Jennifer, committee member; Conroy, Samantha, committee member (Colorado State University. Libraries, 2018)
The subject of job satisfaction is one of the most highly researched topics among organizational psychology (Lu, Barriball, Zhang, & While, 2012). However, only few studies have examined factors of job satisfaction among interior designers due, in part, to infancy of the profession (e.g., Hill, Hegde, & Matthews, 2014). The purpose of this study was to compose a portrait of female interior design professionals currently employed in the workplace and explored the factors impacting their perceived job satisfaction or dissatisfaction. Twelve female interior designers from three career phases (early, mid, and late career) were interviewed to gain diverse perspectives of job satisfaction. Participants were asked to draw the way they felt about their work based on Marcus' (1995) drawing elicitation method. Then interviews were performed using their drawings as a starting point for discussion, along with semi-structured questions guided by the conceptual framework developed for this study from two career phase models (AIA, 2017; Mainiero & Sullivan, 2005) and literature review. Findings suggested dynamic relationships between 1) personal-life factors; 2) work culture; 3) professional mindset; 4) relationships; and 5) resources to support creative performance at work. Participants felt greatest job satisfaction when optimal creative performance was bolstered by ideal conditions with respect to work culture, relationships, and resources when personal-life factors placed pressure on their lives. Furthermore, professional well-being seemed to be largely shaped by professional authenticity and its development through meaning-making tasks and achievements.
Keywords: interior designers; optimal engagement; job satisfaction; career phases